Cardiac rehabilitation using the Family-Centered Empowerment Model versus home-based cardiac rehabilitation in patients with myocardial infarction: a randomised controlled trial. Issue 1 (19th April 2016) - Vahedian-Azimi, Amir; Miller, Andrew C; Hajiesmaieli, Mohammadreza; Kangasniemi, Mari; Alhani, Fatemah; Jelvehmoghaddam, Hosseinali; Fathi, Mohammad; Farzanegan, Behrooz; Ardehali, Seyed H; Hatamian, Sevak; Gahremani, Mehdi; Mosavinasab, Seyed M M; et al.
Abstract : Objective: To determine if a hybrid cardiac rehabilitation (CR) programme using the Family-Centered Empowerment Model (FCEM) as compared with standard CR will improve patient quality of life, perceived stress and state anxiety of patients with myocardial infarction (MI). Methods: We conducted a randomised controlled trial in which patients received either standard home CR or CR using the FCEM strategy. Patient empowerment was measured with FCEM questionnaires preintervention and postintervention for a total of 9 assessments. Quality of life, perceived stress, and state and trait anxiety were assessed using the 36-Item Short Form Health Survey (SF-36), the 14-item Perceived Stress, and the 20-item State and 20-item Trait Anxiety questionnaires, respectively. Results: 70 patients were randomised. Baseline characteristics were similar. Ejection fraction was significantly higher in the intervention group at measurements 2 (p=0.01) and 3 (p=0.001). Exercise tolerance measured as walking distance was significantly improved in the intervention group throughout the study. The quality of life results in the FCEM group showed significant improvement both within the group over time (p<0.0001) and when compared with control (p<0.0001). Similarly, the perceived stress and state anxiety results showed significant improvement both within the FCEM group over time (p<0.0001) and when compared with control (p<0.0001). No significant difference was found either within or between groups for trait anxiety. Conclusions: The family-centred empowerment model may be an effective hybrid cardiac rehabilitation method for improving the physical and mental health of patients post-MI; however, further study is needed to validate these findings. Clinical Trials.gov identifier NCT02402582 . Trial registration number: NCT02402582.